Clapskates at Nagano: World records tumble in speed skating - Allinger, T. L. (Sportscience, 1998)
World records in speed skating improved by an average of 1.9% in this Olympic year, compared with only 0.7% in the 1994 Olympic year. Widespread use of clapskates this season is the most likely reason for the increase in performance, but thin rubber strips on skinsuits may have contributed by reducing wind resistance.